2017
DOI: 10.1515/aoas-2016-0062
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of probiotics in poultry exposed to heat stress – a review

Abstract: heat-related stress has become a serious problem in poultry industry along with the global temperatures rise. heat stress causes detrimental effects on physiology, immunology and microbiology resulting in abnormalities and impaired performances of birds. several nutritional strategies have been conducted to counteract the detrimental effects of heat stress in poultry, including dietary supplementation of probiotics. this strategy has been proposed to ameliorate the intestinal ecosystem, physiological condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 13 publications
1
65
0
1
Order By: Relevance
“…Our finding may therefore suggest that CAS and C. crassa were able to reverse the increased LDL level in HS broilers. The mechanisms through which CAS and C. crassa lowered the LDL level of HS birds are largely unknown, but antioxidants in CAS and probiotic and antioxidant properties in the fungus seemed to control corticosterone secretion (Sugiharto et al, 2016a) resulting in lowered LDL level in HS birds. Indeed, Yuan et al (2008) reported that plasma LDL as well as triglyceride increased with the increased level of corticosterone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our finding may therefore suggest that CAS and C. crassa were able to reverse the increased LDL level in HS broilers. The mechanisms through which CAS and C. crassa lowered the LDL level of HS birds are largely unknown, but antioxidants in CAS and probiotic and antioxidant properties in the fungus seemed to control corticosterone secretion (Sugiharto et al, 2016a) resulting in lowered LDL level in HS birds. Indeed, Yuan et al (2008) reported that plasma LDL as well as triglyceride increased with the increased level of corticosterone.…”
Section: Discussionmentioning
confidence: 99%
“…The HS has been attributed to the oxidative stress in broiler chicks (Sugiharto et al, 2016a). As a natural protective response against oxidative stress (Sohail et al, 2011;Akbarian et al, 2016), serum total antioxidants have been reported to be increased in HS birds (Sohail et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feed additives were able to fulfill this gap through interactions with gut microbiota and contributions to the health of the host (4). Using probiotics as feed additives can initiate resistance to bacterial colonization, and promote the host mucosal immunity for minimizing pathogen load (5).…”
Section: Introductionmentioning
confidence: 99%
“…In such case, antioxidants is essential to protect the birds from oxidative damage (Sugiharto et al, 2017a). Broiler feeds available in the market have actually been supplemented with antioxidants.…”
Section: Introductionmentioning
confidence: 99%